"The Kingdom and the Glory": The Articulated Inoperativity of Power (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
The starting point of this essay is the internal difference in the concept of power, the issue of authority and its relation to the act. The authority operates as both the assumed perfect coincidence of act and law, and as the pure externality of authority to law. This complex structure is the real essence of power in the West, government, whose main signature, The Kingdom and the Glory will go on to argue, has been that of oikonomia or economy. Finally, the paper will examine the notion of inoperativity, concept that reveals the total structure of the system. What we can say however is that until the signatures of power are themselves revealed in their inoperativity, the oft promised key to the totality of the Homo Sacer project, remains unintelligible. It is for this reason that The Kingdom and the Glory may come to be seen not only as one of Agamben’s most important statements, but as the fundamental work of political philosophy of our age.